Factors Associated with Abdominal Obesity among Reproductive Age Women of Kaski District - Narayan Tripathi; Bijaya Parajuli; Arun Koirala; Rojana Dhakal Joshi (Journal of Karnali Academy of Health Sciences, 2022)
Background: Obesity is increasing at an alarming rate and has now become a global public health problem. Reproductive-age women who are obese are at increased risk of infertility, miscarriage and other adverse pregnancy outcomes. The risk of fetal anomalies and congenital heart disease could too increase in the offspring of such women. In view of these considerations, this study aimed to assess the factors associated with abdominal obesity among reproductive-age women of the Kaski district.